A Strategy for Using Instagram as A Promotional Media for New Student Admissions - Ima Soumena; H. Muh. Akbar; Muhammad Yusuf Ar (Journal La Sociale, 2026)
The background of this research is based on the importance of higher education institutions adapting to advancements in information technology, particularly social media, as effective communication channels to reach younger generations. The approach used is qualitative descriptive, with data collected through in-depth interviews with the admissions management, social media administrators, and students, as well as observations of promotional activities on the official Instagram account of the campus. The data analysis was conducted thematically to identify strategies, supporting factors, and obstacles in utilizing Instagram. The results indicate that STIKes Maluku Husada leverages Instagram through visual content such as posters, infographics, short videos, and interactive features like stories, reels, and live sessions to disseminate information about the new student admission process. Supporting factors for success include the high usage of Instagram among prospective students, visual content appeal, and active student participation in the promotional process. However, challenges such as inconsistent content, limited human resources, and underutilized paid promotion features (Instagram Ads) were also identified. The conclusion of this research suggests that Instagram has significant potential as a promotional media for higher education institutions like STIKes Maluku Husada. To improve its effectiveness, better social media management, enhanced content quality, and sustainable digital marketing strategies are necessary.